Combined arms warfare in Israeli military history : from the War of Independence to Operation Protective Edge - Rodman, David (Brighton ; Chicago ; Toronto : Sussex Academic Press, 2019)
Combined arms warfare (CAW) -- the integration of different arms on the battlefield (e.g., armor, infantry, artillery, aircraft, and engineers) in order to achieve maximal efficiency there -- is as old as war itself. Every army across both time and space that has engaged in combat has practiced one version or another of CAW, whether consciously or otherwise. The Israel Defenxse Forces (IDF) has been no exception to the rule. This book traces the Israeli experience with CAW from the countrys War of Independence in 194749 (against a coalition of Arab states) through Operation Protective Edge in 2014 (against a coalition of Hamas-led terrorist/insurgent groups). It describes and analyzes the IDFs practice of CAW in each interstate war (IW), asymmetrical war (AW), and low-intensity conflict (LIC) that Israel has fought since the countrys establishment in the mid-twentieth century. The book also highlights the Israeli approach to CAW in respect of special operations (SPEC OPS). With no end in sight to the ArabIsraeli conflict, and with further hostilities between Israel and its neighbors virtually assured in the future, Combined Arms Warfare in Israeli Military History constitutes an essential addition to the literature about Middle Eastern warfare. This book is aimed primarily at the academic and research community, but it is fully accessible to anyone with an interest in Israeli military history.
Cover; Dedication; Title Page; Copyright; Contents; List of Abbreviations; List of Illustrations; Preface; Introduction The Essence of Combined Arms Warfare; 1 The War of Independence and the Sinai Campaign; 2 The Six-Day War; 3 The War of Attrition; 4 The Yom Kippur War; 5 The Lebanon War; Plates; 6 The Second Lebanon and Gaza Wars; 7 Between Wars; 8 "In Time of Peace, Conflict, or War"; Conclusion The Benefits of Combined Arms Warfare; Glossary of Technical Terms; Notes; Bibliography; Index; Back Cover
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Israel. -- Tseva haganah le-Yiśraʼel -- History; Israel. -- Tseva haganah le-Yiśraʼel; Israel -- History, Military; Unified operations (Military science); Opérations interarmes (Science militaire); HISTORY -- Military -- Other; TECHNOLOGY & ENGINEERING -- Military Science; Unified operations (Military science); Israel; History; Military history